BMP‐TAK1 (MAP3K7) Induces Adipocyte Differentiation Through PPARγ Signaling. Issue 1 (27th June 2016) - Zhang, Yongchun; O'Keefe, Regis J.; Jonason, Jennifer H.
ABSTRACT: BMPs have been shown to promote adipocyte differentiation through SMAD‐dependent signaling. However, the role of TGF‐β‐activated kinase 1 (TAK1) in non‐canonical BMP signaling in adipocyte differentiation remains unclear. Here, we show that TAK1 inhibition decreases lipid accumulation in C3H10T1/2 mesenchymal stem cells (MSCs) induced to differentiate into adipocytes. TAK1 knockdown by siRNA further confirms that TAK1 is required for adipocyte commitment of MSCs. Additionally, TAK1 knockdown inhibits adipogenesis of 3T3‐L1 preadipocytes, indicating that TAK1 is not only needed for adipocyte commitment, but also required for adipocyte terminal differentiation. Furthermore, TAK1 ablation specifically in adipocytes reduced high fat diet‐induced weight gain and improved glucose tolerance. Mechanistically, we demonstrate that TAK1 is required for PPARγ transactivation and promotes PPARγ transcriptional activity synergistically with TAK1 binding protein 1 (TAB1). Collectively, our results demonstrate that TAK1 plays a critical role in BMP‐mediated adipocyte differentiation. J. Cell. Biochem. 118: 204–210, 2017. © 2016 Wiley Periodicals, Inc. Abstract : TAK1 plays a critical role in BMP2‐mediated adipocyte lineage commitment and terminal differentiation via positive regulation of PPARγ transcriptional activity. In vivo, TAK1 deletion from adipocytes results in suppression of high‐fat diet‐induced weight gain and glucose intolerance.